Design and implementation of weather fore casting system based on cloud computing and data mining techniques - P, Rajarajeswari; Pradeep kumar, J; Vasumathi, D (International Journal of Engineering and Technology, 2018)
Software engineering is an engineering discipline which is used to analyze, modeling and development of the system. Normally Weather conditions are changing continuously with respective to atmospheric conditions. In the phase of modeling of the Weather fore casting system is performed by taking the data which is collected on atmospheric conditions and record temperature, rainfall, humidity and other parameters. The main objective of this paper is focused on Design and implementation of Weather forecasting system. Weather forecasting model is prepared by using Cloud computing and Data mining techniques. This System is analyzed by using temperature, rainfall conditions. Statistical framework is provided on Modeling for surface process of weather forecasting with Data assimilation. This paper presents the Conceptual level architecture of Weather prediction model by using decision tree. Proposed algorithm is used for the construction of decision tree. Weather forecasting report is implemented by using Android.